Evolution of oxidative stress research in liver cirrhosis: A 30-Year bibliometric review (1992–2025) - Kurmangaliyeva, Saulesh; Baktikulova, Kristina; Kurmangaliyev, Kairat; Tissin , Konstantin; Abenova , Nurgul; Makashova, Mengtay; Sarbulatova, Anargul (Acta Biomedica Atenei Parmensis, 2025)
Background: Oxidative stress plays a pivotal role in the pathogenesis of liver cirrhosis, yet scientific research on this topic remains fragmented. The main objective of this study was to provide a systematic overview of global research activity on oxidative stress in liver cirrhosis through bibliometric analysis. Methods: We conducted a bibliometric analysis of publications on oxidative stress in liver cirrhosis from 1992 to 2025, using data from the Scopus and Web of Science databases. Analytical tools included R (Biblioshiny) and VOSviewer for data processing and visualization. We evaluated publication trends, leading countries, institutions, authors, journals, collaboration networks, and research themes. Results: A total of 318 scientific articles from 196 journals were analyzed, involving more than 2,000 authors. The United States, China, and Italy were the top contributors. The University of Barcelona emerged as the most prolific institution. Keyword co-occurrence analysis identified major research clusters focused on mitochondrial dysfunction, antioxidant therapies, inflammatory processes, and biomarker development. Key research terms, such as "lipid peroxidation," "insulin resistance," and "gene regulation," reflect a growing interest in both molecular mechanisms and clinical applications. Conclusion: The study highlights a steady rise in research activity and underscores the need for interdisciplinary collaboration. These findings offer valuable insights to guide future scientific and clinical investigations.